Talking body: the effect of body and voice anthropomorphism on perception of social agents - Haresamudram, Kashyap; Torre, Ilaria; Behling, Magnus; Wagner, Christoph; Larsson, Stefan (Frontiers in Robotics and AI, 2024)
IntroductionIn human-agent interaction, trust is often measured using human-trust constructs such as competence, benevolence, and integrity, however, it is unclear whether technology-trust constructs such as functionality, helpfulness, and reliability are more suitable. There is also evidence that perception of “humanness” measured through anthropomorphism varies based on the characteristics of the agent, but dimensions of anthropomorphism are not highlighted in empirical studies.MethodsIn order to study how different embodiments and qualities of speech of agents influence type of trust and dimensions of anthropomorphism in perception of the agent, we conducted an experiment using two agent “bodies”, a speaker and robot, employing four levels of “humanness of voice”, and measured perception of the agent using human-trust, technology-trust, and Godspeed series questionnaires.ResultsWe found that the agents elicit both human and technology conceptions of trust with no significant difference, that differences in body and voice of an agent have no significant impact on trust, even though body and voice are both independently significant in anthropomorphism perception.DiscussionInterestingly, the results indicate that voice may be a stronger characteristic in influencing the perception of agents (not relating to trust) than physical appearance or body. We discuss the implications of our findings for research on human-agent interaction and highlight future research areas.